2013
DOI: 10.1104/pp.112.211938
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming Can Negate the Expected CO2 Stimulation in Photosynthesis and Productivity for Soybean Grown in the Midwestern United States    

Abstract: Extensive evidence shows that increasing carbon dioxide concentration ([CO 2 ]) stimulates, and increasing temperature decreases, both net photosynthetic carbon assimilation (A) and biomass production for C 3 plants. However the [CO 2 ]-induced stimulation in A is projected to increase further with warmer temperature. While the influence of increasing temperature and [CO 2 ], independent of each other, on A and biomass production have been widely investigated, the interaction between these two major global cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
179
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(204 citation statements)
references
References 45 publications
9
179
1
4
Order By: Relevance
“…However, recent evidence suggests that elevated temperatures have a negative impact on the same physiological processes, and that the combined effect of both increased CO 2 and temperature may lead to decreased photosynthesis and biomass production (Ruiz-Vera et al 2013). In addition, heat stress during pollination will increase the vulnerability of several commodity crops (Sage and Kubien 2007;Semenov and Shewry 2011), especially in areas where crops are grown close to the critical temperature limit for photosynthesis (Ruiz-Vera et al 2013). In contrast, higher temperatures may prolong cultivation seasons and lead to higher yields in northern latitudes and colder areas (Eckersten et al 2011).…”
Section: Climate Changementioning
confidence: 99%
“…However, recent evidence suggests that elevated temperatures have a negative impact on the same physiological processes, and that the combined effect of both increased CO 2 and temperature may lead to decreased photosynthesis and biomass production (Ruiz-Vera et al 2013). In addition, heat stress during pollination will increase the vulnerability of several commodity crops (Sage and Kubien 2007;Semenov and Shewry 2011), especially in areas where crops are grown close to the critical temperature limit for photosynthesis (Ruiz-Vera et al 2013). In contrast, higher temperatures may prolong cultivation seasons and lead to higher yields in northern latitudes and colder areas (Eckersten et al 2011).…”
Section: Climate Changementioning
confidence: 99%
“…It implies that the harvest index of soybean would decrease under future climate scenarios with increased temperature and CO 2 concentration. It has been reported that the harvest index of soybean decreases under doubling of the CO 2 concentration (Cure and Acock 1986), and with increased temperature through reductions of pod and seed numbers (Ruiz-Vera et al 2013;Tacarindua et al 2013). Ruiz-Vera et al (2013) concluded that under future climate conditions, the combined effects of elevated CO 2 concentration and higher temperature would likely reduce growth due to overriding environmental factors, but this conclusion was based on current crop cultivars.…”
Section: Response To Climate Changementioning
confidence: 99%
“…It has been reported that the harvest index of soybean decreases under doubling of the CO 2 concentration (Cure and Acock 1986), and with increased temperature through reductions of pod and seed numbers (Ruiz-Vera et al 2013;Tacarindua et al 2013). Ruiz-Vera et al (2013) concluded that under future climate conditions, the combined effects of elevated CO 2 concentration and higher temperature would likely reduce growth due to overriding environmental factors, but this conclusion was based on current crop cultivars. From (Morrison et al 1999;Rowntree et al 2014), and breeding efforts to keep high harvest index will likely continue.…”
Section: Response To Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Krituliai, nors ir negausūs, labai suaktyvina CO 2 emisijas iš dirvožemio (Lee et al, 2004;Yuste et al, 2003), o fotosintezės asimiliuotas CO 2 kiekis didėja priklausomai nuo šviesos intensyvumo iki šviesos įsotinimo tarpsnio. Fotosintezės asimiliuoto CO 2 kiekio intensyvumas priklauso ne tik nuo absorbuojamo anglies dioksido kiekio, bet ir nuo esamo drėgmės ir temperatūros, kuri tiesiogiai paveikia fermento aktyvumą (Ruiz-Vera et al, 2013). Tikslių anglies apykaitos duomenų intensyvios žemdirbystės pasėlių agroekosistemose nėra sukaupta, todėl sezoninis C apykaitos kitimo nustatymas būtų reikšmingas formuojant C balansą CO 2 emisijų mažinimo kryptimi bei prognozuojant jų pokyčius.…”
unclassified